CACNA1C rs1006737 SNP increases the risk of essential hypertension in both Chinese Han and ethnic Russian people of Northeast Asia. Issue 8 (26th February 2021) - Zhang, Hao; Pushkarev, Boris; Zhou, Jiexin; Mu, Yuyuan; Bolshakova, Olga; Shrestha, Sandeep; Wang, Ningning; Jian, Baiyu; Jin, Ming; Zhang, Keyong; Cong, Mingyu; Liu, Jicheng; et al.
Abstract : Abstract: Voltage-gated Ca 2+ channels play a key role in the regulation of arterial tone and blood pressure. The aim of this study was to determine whether the association of calcium voltage-gated channel subunit alpha1 C (CACNA1C) rs1006737 with essential hypertension (EH) exists in both Chinese Han and ethnic Russian populations of Northeast Asia. We used a case-control study of 2 ethnic groups in the same latitude geographical area to investigate the association between the susceptibility of EH and rs1006737 polymorphism. A total of 1512 EH patients and 1690 controls in Chinese Han people (Heilongjiang Provence, China), 250 EH patients, and 250 controls in ethnic Russian people (Chita, Russia), participated in this study. All participants were genotyped using the TaqMan SNP genotyping assay (Agena Company). Baseline characteristics and the minor allele frequencies of rs1006737 vary substantially among common Chinese Han and ethnic Russian people. Allele A was found to be a risk factor for EH in Chinese Han [(odds ratio) OR 1.705, (confidence interval) 95% CI: 1.332–2.182, P  < .001] and ethnic Russian (OR 1.437; 95% CI: 1.110–1.860, P  = .006). The GA genotype was significantly associated with an increased risk of hypertension (OR 1.538, 95% CI: 1.188–1.991, P  = .001) for Chinese Han people, and the AA genotype (OR 2.412, 95% CI: 1.348–4.318, P  = .003) for ethnic Russian people. The results of this study indicate that the A allele of the variant rs1006737 in the CACNA1C gene may be a useful genetic marker for EH risk prediction in Chinese Han and ethnic Russian populations.